PROBLEMS OF ETHNOPOLITICAL DEVELOPMENT OF THE KYRGYZ PEOPLE IN THE SOVIET PERIOD (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Soviet nation-building played an exceptional role in the ethnic history of the Kyrgyz. It was of a complex nature and implied not only the realization of the principle of national self-determination, which was embodied for the Kyrgyz through the consistent elevation of the status of national statehood within the USSR – from an autonomous region to an autonomous and then a union republic. The author analyzes the main tools and the role of various actors in the policy of Soviet nation-building. Special attention is paid to the specifics of federal construction in the 1920s, the role of the ethnopolitical elites of the Central Asian region in interaction with the center and among themselves. The article examines the problems of organization as a tool of nation-building, the contribution of the leading participants in this process, including the intelligentsia, teaching staff educational tools and propaganda.
Keywords: Soviet nation-building, ethnopolitical elite, federalism, autonomy.